ANALISIS PEMANTAUAN DETEKTOR CAIRAN INFUS BERBASIS MIKROKONTROLER ATMEGA 8535 - Fitria Priyulida; Ruby Angelika Siringoringo (JURNAL MUTIARA ELEKTROMEDIK, 2021)
In healthy care , the comfortable of patient is primary. Therefore, the healthy world trying to improve the quality of health services with emphasis on comfort and safety for patients as the primary starting point. To improve the quality of service , started from simple things like calling anurse to replace the infusion to be exhausted. Patients not realize that the infusion has finis hedeither while awake or not awake oftenly. Causing the blood up into the hose, and the hose will clogged because ofthe clots of blood sleft in the hose. Making Detector Fluid of Infusion Based Microcontroller ATMEGA 8535 can solve simple issues that will detect the presence or absence ofintravenous fluids by sending signals using the wireless system to call a nurse instead of the callbutton nurses and to prevent the above problems happened with the method senders of modulation signal ASK (Amplitude Shift keying). The author analyzes the photodiode sensor as a detectorthat detects intravenous fluids , and connect it to the microcontroller as the CPU (Central Processing Units) to processing data which sent by sensor. This prototype has advantages and dis advantages . As a prototype , this tool is appropriate to be applied directly in the health service. And for better results, the use ofthis prototypeis placed in a room with the low intensity of light to support the performance of the sensor which very sensitive to light.